PEMBUATAN PAPAN SERAT BERKEPARATAN SEDANG DARI KAYU DAUN LEBAR DENGAN PROSES PAPAN MEKANIS (thermomechanical of medium density fibreboard (MDI) from hardware) - Kayano purba (Jurnal Penelitian Hasil Hutan, 1993)
This paper deals with an experiment investigating the effect of presteaning time on the properties of medium density fibreboard. The boards were made of 15 wood species mixtures with an equal weight proportion of four specific gravity groups i,e 0.31 – 0.45; 0,46 – 0,60; 0,61 – 0,75; and 0.76 – 0.90.Pulp preparations were carried out by using thermo mechanically at 4 kg/cm2 for 10, 15 and 20 minutes and refined for 10 minutes. The sheets were formed by using the laboratory wet felting process. Cold pressing ( room temperature) and hot pressing (170°C) were conducted at 45 kg/cm2 for 5 minutes and 20 kg/cm2 for 40minutes, respectively.The experiment’s result also showed that the tensile strength parallel to surface, modulus of rupture, modulus of elasticity. Density, water absorption, thickness swelling and volume swelling of fiberboard were not significantly affected by the presteaming time, specific gravity and interaction of the both factors. It was also reviewed that an increasing specific gravity tended to lower the intodulus of rupture, tensile strength parallel to surface and modulus of elasticity, and tended to increase thickness swelling, volume swelling and water absorption.In general , the properties of the medium density fibreboard (density, water absorption, modulus of rupture and modulus of elasticity) are comparable to those of the FAO standard requirements, but the tensile strength parallel to surface is tess than that of the FAO standard.